Genomic heterogeneity in core-binding factor acute myeloid leukemia and its clinical implication - Jahn, Nikolaus; Terzer, Tobias; Sträng, Eric; Dolnik, Anna; Cocciardi, Sibylle; Panina, Ekaterina; Corbacioglu, Andrea; Herzig, Julia; Weber, Daniela; Schrade, Anika; Götze, Katharina; Schröder, Thomas; et al. (Blood advances, 2020)
Core-binding factor (CBF) acute myeloid leukemia (AML) encompasses AML with inv(16)(p13.1q22) and AML with t(8;21)(q22;q22.1). Despite sharing a common pathogenic mechanism involving rearrangements of the CBF transcriptional complex, there is growing evidence for considerable genotypic heterogeneity. We comprehensively characterized the mutational landscape of 350 adult CBF-AML [inv(16): n = 160, t(8;21): n = 190] performing targeted sequencing of 230 myeloid cancer-associated genes. Apart from common mutations in signaling genes, mainly NRAS, KIT, and FLT3, both CBF-AML entities demonstrated a remarkably diverse pattern with respect to the underlying cooperating molecular events, in particular in genes encoding for epigenetic modifiers and the cohesin complex. In addition, recurrent mutations in novel collaborating candidate genes such as SRCAP (5% overall) and DNM2 (6% of t(8;21) AML) were identified. Moreover, aberrations altering transcription and differentiation occurred at earlier leukemic stages and preceded mutations impairing proliferation. Lasso-penalized models revealed an inferior prognosis for t(8;21) AML, trisomy 8, as well as FLT3 and KIT exon 17 mutations, whereas NRAS and WT1 mutations conferred superior prognosis. Interestingly, clonal heterogeneity was associated with a favorable prognosis. When entering mutations by functional groups in the model, mutations in genes of the methylation group (ie, DNMT3A, TET2) had a strong negative prognostic impact.
Gesehen am 10.03.2022